A Comparison of Carbon Molecular Sieve (CMS) Membranes with Polymer Blend CMS Membranes for Gas Permeation Applications - Huda, W.Z. Wan Nurul; Ahmad, M.A. (ASEAN Journal of Chemical Engineering, 2012)
In this work, polyetherimide (PEI) was used as a main precursor to prepare carbon molecular sieve (CMS) membranes coated on a porous α-alumina disk via inert pyrolysis process. The PEI precursor was modified by blending with poly(ethylene glycol) (PEG) and its effect on the gas transport property of carbon membrane pyrolyzed at 873K was examined. The coating solution was prepared by PEI diluted in N-methylpyrrolidone (NMP) and coated onto support by dip-coating technique. Uniform CMS membranes were obtained by repeated dip-coating and pyrolysis of PEI and PEI/PEG. The structure and the single gas permeation properties of PEI and PEI/PEG CMS membrane were investigated.The thermal stability of CMS membranes prepared was determined by thermal gravimetric analysis (TGA). Elemental analysis, scanning electron microscopy (SEM), and Attenuated Total Reflectance Infrared (ATR-IR) Spectroscopy were employed to characterize the resulting membranes. The gas permeation of the CMS membranes was tested using three gases: methane, carbon dioxide, and oxygen and performed at 298K. The best performance was obtained by using PEI/PEG CMS membrane, whereby CO2 permeability should be 400.44x10-10 mol.m-2.s-1.Pa-1.